Pengembangan Multimedia Pembelajaran Interaktif Berbasis Grafis Untuk Mata Pelajaran Pemrograman Dasar Menggunakan Model APPED Pada Jurusan Multimedia di SMK Negeri 4 Malang - Hanif Aulia Kusuma; Hanifah Muslimah Az-zahra; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
One of the impacts of the change in curriculum structure (from the 2006 curriculum to the 2013 curriculum) is that there are basic programming subjects in the Department of Multimedia class X which previously did not exist. This has caused problems, including the lack of relevant learning resources and the results of evaluating the function material while carrying out Lesson Study in the Multimedia-C class X, 28 students out of 37 students scored below the KKM (Minimum completeness criteria). These problems need to be developed in Interactive Learning Multimedia (MPI) using the APPED model to improve student learning outcomes. The results of the MPI product evaluation were declared valid by researchers at the ongoing evaluation stage, for the alpha test stage the assessment of material experts was 97.80% and included in the category of "very valid", for the assessment of media experts which amounted to 68.90% and included the category " valid ", and for the assessment of instructional experts that is equal to 82.50% and belongs to the category of" very valid ", then MPI products are distributed to determine the level of effectiveness of the product in learning by conducting different tests using the Wilcoxon signed-rank test and producing Asymp. Sig. (2-tailed) of 0,000 because the value is lower than 0.050, it can be concluded that MPI products are considered effective.